ADORE: An Adaptation-Oriented Requirement Modeling Approach for Systems of Systems - Maciel, Marcia M. S. S.; Maciel, Filipe; Maia, Paulo Henrique; Oliveira, Francisco C. M. B. (Companion Proceedings of the Brazilian Symposium on Software Engineering (SBES); 2019: Companion Proceedings of the 33th Brazilian Symposium on Software Engineering, 2020)
The composition of several independently manageable and operable systems in order to create a system of systems may require adaptations due to the rise of emergent behaviours. An inadequate identification, by the requirement engineer, of how a new behaviour impacts the constituent systems could lead to conflicts and poor operation of the system. Therefore, identifying and resolving such scenarios is crucial for defining adaptation strategies as well assuring the achievement of the system global requirements. In this paper, a systematic adaptation-oriented requirement modeling approach for Systems of Systems, called ADORE, is presented. The proposed approach relies on the Cognitive Work Analysis (CWA) framework and Goal-oriented Requirements Engineering concepts to define three phases, each of them with a specific output model, that aim at modelling the system domain, identifying the collaborative tasks and analysing the scenarios and adaptations strategies. The approach is used to model a drone medical delivery system in order to demonstrate its applicability.